Autoantibodies to the GLUT-2 glucose transporter of beta cells in insulin-dependent diabetes mellitus of recent onset. - Inman, L R (1993)
Purified immunoglobulin G (IgG) from the serum of patients with insulin-dependent diabetes mellitus (IDDM) of recent onset inhibits high-Km uptake of 3-O-methyl-beta-D-glucose by rat pancreatic islets. To determine if the inhibition is the result of antibodies against GLUT-2, the high-Km glucose transporter of beta cells, we incubated IDDM sera with rat islet cells and with AtT-20ins cells transfected to express GLUT-2. IDDM sera inhibited glucose uptake in islet cells and in GLUT-2-expressing AtT-20ins cells but not in AtT-20ins cells transfected to express the low-Km isoform, GLUT-1. In 24 of 30 (77%) patients with newly diagnosed IDDM, IgG binding as measured by immunofluorescence and flow cytometry of the cells transfected to express GLUT-2 was > 2 standard deviations from the mean of the nondiabetic population; 29 of 31 (96%) of nondiabetic children were negative (P < 0.0001). Increased IgG binding could be removed by absorption with GLUT-2-expressing cells but not with GLUT-1-expressing cells. We conclude that most patients with IDDM of recent onset have autoantibodies to GLUT-2.